"Wise Mothers," "Mom Bugs," and Pyŏngmat (Twisted Tastes): The Limits of Maternal Emotional Expression in South Korean Webtoons. - Tilland, Bonnie (Korean Studies, 2024)
This article examines the representation of South Korean mothers in webtoons, specifically focusing on the emotional expressions that are allowed and those that are considered taboo. It compares South Korean "mom content" to similar trends in Japan and explores the use of humor as a means of conveying the maternal experience. The analysis is based on a selection of webtoons that address pregnancy, childbirth, and parenting, highlighting the role of webtoons in providing a space for community and catharsis for mothers in South Korea. The article also discusses the influence of mom blogs in other countries and the popularity of mom cafes in South Korea. It concludes by examining the ways in which webtoons challenge traditional narratives of motherhood and provide a platform for mothers to share their experiences.